Product promotions in online supermarkets: prevalence of 'High Fat Sugar Salt' (HFSS) products and labelling characteristics - Lewis W Wallis; Sally G Moore (Cambridge University Press, 2023)
Abstract Objective: To evaluate the prevalence of 'High Fat Sugar Salt' (HFSS) products and front-of-pack nutrition labelling (FOPNL) characteristics across promoted products in UK online supermarkets. Design: A cross-sectional survey conducted (December 2021-January 2022) on promoted products. Data on ingredients, nutritional composition and display of FOPNL were collected from product webpages. The UK's Nutrient Profiling Model and Multiple Traffic Light criteria were used to determine HFSS status and possession of inherent red traffic lights (iRTL), respectively. Data analysis determined the prevalence (i.e. percentage of products of the total number of products sampled) of HFSS; FOPNL and possession of iRTL. Chi-squared tests explored associations between these. Setting: Three major UK online supermarket retailer websites. Participants: Product 'multibuy' and 'entrance' promotions, from selected product categories. Results: Among the sampled 625 promoted products, the prevalence of HFSS was greater in entrance (73 %) compared with multibuy (41 %) promotions (χ2 (1) = 34, P < 0·05), with variations in the former across retailers (49-92 %). The prevalence of HFSS products in multibuy promotions offered by two retailers varied by category (i.e. Confectionery 94-97 %, Yogurts 20-20 %, Soft Drinks 16-33 %, Ready Meals 1·4-18 %). Not all promoted products displayed FOPNL on webpages (70 %) or images (52 %). A number of iRTL were found to be possessed by both HFSS and non-HFSS-promoted products. Conclusions: Prior to the 2022 implementation of Regulations restricting these, HFSS products were promoted in online supermarkets with varying display of FOPNL and possession of iRTL. Findings support future policy evaluation and mandatory digital FOPNL.